2012
DOI: 10.1098/rsif.2012.0016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico investigations of disc nucleus replacement

Abstract: Currently, numerous hydrogels are under examination as potential nucleus replacements. The clinical success, however, depends on how well the mechanical function of the host structure is restored. This study aimed to evaluate the extent to and mechanisms by which surgery for nucleus replacements influence the mechanical behaviour of the disc. The effects of an annulus defect with and without nucleus replacement on disc height and nucleus pressure were measured using 24 ovine motion segments. The following case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Finite element analyses showed that a destroyed interface is one possible reason for the strong differences between DEF-NUC and INTACT (Reitmaier et al, 2012). The model predicted a 10% drop in IDP during the creep phases after replacing the native nucleus material.…”
Section: Discussionmentioning
confidence: 90%
“…Finite element analyses showed that a destroyed interface is one possible reason for the strong differences between DEF-NUC and INTACT (Reitmaier et al, 2012). The model predicted a 10% drop in IDP during the creep phases after replacing the native nucleus material.…”
Section: Discussionmentioning
confidence: 90%
“…Lasting 24 hours, the time frame of IDP measurement in the current study is comparably short and degenerative changes due to disc puncture therefore are not expected. Additionally, a 4 mm cut in the annulus was shown not to significantly impair axial compressive stiffness and IDP of the ovine intervertebral disc [45,46]. …”
Section: Discussionmentioning
confidence: 99%
“…Mechanical evaluation of nucleus replacements often focuses on the intrinsic mechanical properties of the gel and its immediate effects on disc mechanical response [18][19][20][21][22]. More extensive mechanical testing is completed with the aim of testing failure properties [23,24].…”
Section: Introductionmentioning
confidence: 99%